Sulforaphane Ameliorates Metabolic Changes Associated With Status Epilepticus in Immature Rats - Daněk, Jan; Danačíková, Šárka; Kala, David; Svoboda, Jan; Kapoor, Sonam; Pošusta, Antonín; Folbergrová, Jaroslava; Tauchmannová, Kateřina; Mráček, Tomáš; Otáhal, Jakub (Frontiers in Cellular Neuroscience, 2022)
Status epilepticus (SE) is a common paediatric emergency with the highest incidence in the neonatal period and is a well-known epileptogenic insult. As previously established in various experimental and human studies, SE induces long-term alterations to brain metabolism, alterations that directly contribute to the development of epilepsy. To influence these changes, organic isothiocyanate compound sulforaphane (SFN) has been used in the present study for its known effect of enhancing antioxidative, cytoprotective, and metabolic cellular properties via the Nrf2 pathway. We have explored the effect of SFN in a model of acquired epilepsy induced by Li-Cl pilocarpine in immature rats (12 days old). Energy metabolites PCr, ATP, glucose, glycogen, and lactate were determined by enzymatic fluorimetric methods during the acute phase of SE. Protein expression was evaluated by Western blot (WB) analysis. Neuronal death was scored on the FluoroJadeB stained brain sections harvested 24 h after SE. To assess the effect of SFN on glucose metabolism we have performed a series of 18F-DG μCT/PET recordings 1 h, 1 day, and 3 weeks after the induction of SE. Responses of cerebral blood flow (CBF) to electrical stimulation and their influence by SFN were evaluated by laser Doppler flowmetry (LDF). We have demonstrated that the Nrf2 pathway is upregulated in the CNS of immature rats after SFN treatment. In the animals that had undergone SE, SFN was responsible for lowering glucose uptake in most regions 1 h after the induction of SE. Moreover, SFN partially reversed hypometabolism observed after 24 h and achieved full reversal at approximately 3 weeks after SE. Since no difference in cell death was observed in SFN treated group, these changes cannot be attributed to differences in neurodegeneration. SFN per se did not affect the glucose uptake at any given time point suggesting that SFN improves endogenous CNS ability to adapt to the epileptogenic insult. Furthermore, we had discovered that SFN improves blood flow and accelerates CBF response to electrical stimulation. Our findings suggest that SFN improves metabolic changes induced by SE which have been identified during epileptogenesis in various animal models of acquired epilepsy.